Manajemen Usaha Rumahan Berbasis Instagram oleh Mahasiswa: Studi Kasus Sistem Pre-Order pada Usaha ‘Nyemilee’ - Dina Aulia; Febrianti Shakira; Zainarti Zainarti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Nyemilee is a student-run homemade fruit salad business that uses a pre-order system and social media to align operations with academic schedules. This qualitative-descriptive study involved interviews, Instagram (@nyemilee.id) observation, and PO documentation. Findings show that PO enhances efficiency, Instagram acts as a digital storefront and customer service tool, while time and demand challenges are managed through scheduling and daily quotas.